Highly sensitive refractive index sensor based on hybrid plasmonic waveguide microring resonator. Issue 2 (2nd April 2020) - Butt, M. A.; Khonina, S. N.; Kazanskiy, N. L.
Abstract : A refractive index (RI) sensor based on straight silicon strip waveguide and a hybrid plasmonic microring resonator is presented. The hybrid waveguide is made up of a Metal-Air-Silicon structure, where the electric field is significantly enhanced in the narrow air gap. The transmission spectrum and electric field distribution of this sensor structure are simulated using Finite Element Method (FEM). Due to a large overlap of the optical field in the hybrid microring resonator and the sensing medium, this sensor can be used for both gas and bio sensing applications. The best sensitivity of 690 nm/RIU and 401 nm/RIU is obtained for gas and bio sensing, respectively. The obtained values are relatively high as compared to conventional dielectric microring resonator sensors. Our proposed sensor design has a potential to find further applications in biomedical science and nanophotonic circuits.